Pengaruh Partisipasi Anggaran dan Akuntabilitas Publik Terhadap Kinerja Manajerial: Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Padang - Rijalul Muhsin; Sany Dwita (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to see the effect of budgetary participation and public accountability on the managerial performance of the Padang City SKPD. The population in this study were structural officials in the SKPD of Padang City, as many as 110 respondents. The sample in this study used purposive sampling technique. The analytical method used is Multiple Linear Regression Analysis. The results of this study indicate that budgetary participation has an effect on the managerial performance of the Padang City SKPD, while public accountability has no effect on the Padang City SKPD managerial performance.